The PINK1/Parkin signaling pathway-mediated mitophagy: a forgotten protagonist in myocardial ischemia/reperfusion injury - Xiaopeng Zhao; Zheng Wang; Lijie Wang; Tao Jiang; Dan Dong; Mingli Sun (Elsevier, 2024)
Myocardial ischemia causes extensive damage, further exacerbated by reperfusion, a phenomenon called myocardial ischemia/reperfusion injury (MIRI). Nowadays, the pathological mechanisms of MIRI have received extensive attention. Oxidative stress, multiple programmed cell deaths, inflammation and others are all essential pathological mechanisms contributing to MIRI. Mitochondria are the energy supply centers of cells. Numerous studies have found that abnormal mitochondrial function is an essential ''culprit'' of MIRI, and mitophagy mediated by the phosphatase and tensin homolog (PTEN)-induced kinase 1 (PINK1)/Parkin signaling pathway is an integral part of maintaining mitochondrial function. Therefore, exploring the association between the PINK1/Parkin signaling pathway-mediated mitophagy and MIRI is crucial. This review will mainly summarize the crucial role of the PINK1/Parkin signaling pathway-mediated mitophagy in MIR-induced several pathological mechanisms and various potential interventions that affect the PINK1/Parkin signaling pathway-mediated mitophagy, thus ameliorating MIRI.